Strategi Manajemen Harian Rakyat Sulsel Menciptakan Brand Awareness Sebagai Koran Referensi Politik Di Sulawesi Selatan - Mahdar; Djalil, Nur Alim; Latief, Sukriansyah S. (Jurnal Dakwah Tabligh, 2024)
This study aims to: knowing the management strategy of Rakyat Sulsel Daily in creating brand awareness as a political reference newspaper in South Sulawesi; knowing the supporting factors of Rakyat Sulsel Daily management strategy in creating brand awareness. Data were analyzed using qualitative descriptive analysis. Based on the research results, it was found that: 1) There are six management strategies of Rakyat Sulsel Daily in creating brand awareness as a political reference newspaper in South Sulawesi. First, strengthening brand identity. Second, increasing visibility. Third, creating a media ecosystem. Fourth, the hyperlocal approach. Fifth, doing media convergence. Sixth, door-to-door marketing.There are three factors supporting the media management strategy of Rakyat Sulsel Daily in creating brand awareness as a political reference newspaper in South Sulawesi, namely human resource support, complete and adequate facilities and infrastructure, and the application of four management functions, namely planning, organizing, actuating, and controlling.